2021
DOI: 10.1007/s11606-021-07011-0
|View full text |Cite
|
Sign up to set email alerts
|

Receipt of Tobacco Treatment and One-Year Smoking Cessation Rates Following Lung Cancer Screening in the Veterans Health Administration

Abstract: BACKGROUND: Implementation of effective smoking cessation interventions in lung cancer screening has been identified as a high-priority research gap, but knowledge of current practices to guide process improvement is limited due to the slow uptake of screening and dearth of data to assess cessation-related practices and outcomes under real-world conditions. OBJECTIVE: To evaluate cessation treatment receipt and 1-year post-screening cessation outcomes within the largest integrated healthcare system in the USA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…In 2 other SCALE trials, Foley et al reported 7-day abstinence rates of 13% at 6 months, and Tremblay et al reported 30-day abstinence rates of 13% to 14%. Clinical observational studies have reported quit rates in the LCS setting of 9% to 14% . Modeling studies support that integrating tobacco treatment with LCS yields cost-benefits of similar magnitude of LCS itself; for example, adding a tobacco cessation intervention with an effectiveness of 15% results in equivalent life-years gained as increasing LCS uptake from 30% to 100% .…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In 2 other SCALE trials, Foley et al reported 7-day abstinence rates of 13% at 6 months, and Tremblay et al reported 30-day abstinence rates of 13% to 14%. Clinical observational studies have reported quit rates in the LCS setting of 9% to 14% . Modeling studies support that integrating tobacco treatment with LCS yields cost-benefits of similar magnitude of LCS itself; for example, adding a tobacco cessation intervention with an effectiveness of 15% results in equivalent life-years gained as increasing LCS uptake from 30% to 100% .…”
Section: Discussionsupporting
confidence: 85%
“…Clinical observational studies have reported quit rates in the LCS setting of 9% to 14%. [33][34][35] Modeling studies support that integrating tobacco treatment with LCS yields cost-benefits of similar magnitude of LCS itself; for example, adding a tobacco cessation intervention with an effectiveness of 15% results in equivalent life-years gained as increasing LCS uptake from 30% to 100%. 36 The quit rates observed in PLUTO suggest that the investment of resources to adopt a chronic care model in the LCS setting would be effective and cost-effective.…”
Section: Discussionmentioning
confidence: 99%
“…Trials that measured smoking cessation all concluded that the smoking cessation rates were above that observed in the general population [177][178][179][180][181]. The optimal strategy for integrating smoking cessation has been the focus of much research [15,174,179,[182][183][184][185][186][187][188][189][190][191][192][193][194]. There are limited data around provision of other services, such as psychological support, within the screening programme.…”
Section: Evidence Reviewmentioning
confidence: 99%
“…A recent study in the VA found high rates of screening among patients undergoing LCS. However, 82% of those identified as tobacco users received neither counseling nor pharmacotherapy, and only 1% of smokers receiving the recommended, most effective form of treatment: behavioral treatment plus pharmacotherapy [ 19 ]. Given the CMS policy change, it is now even more important to build commitment and capacity among LCS programs to implement TUT in their settings.…”
Section: Problemmentioning
confidence: 99%